The effectiveness and cost-effectiveness of the peer-delivered Thinking Healthy Programme for perinatal depression in Pakistan and India: the SHARE study protocol for randomised controlled trials. Issue 1 (December 2015) - Sikander, Siham; Lazarus, Anisha; Bangash, Omer; Fuhr, Daniela; Weobong, Benedict; Krishna, Revathi; Ahmad, Ikhlaq; Weiss, Helen; Price, LeShawndra; Rahman, Atif; Patel, Vikram
Abstract Background Rates of perinatal depression (antenatal and postnatal depression) in South Asia are among the highest in the world. The delivery of effective psychological treatments for perinatal depression through existing health systems is a challenge due to a lack of human resources. This paper reports on a trial protocol that aims to evaluate the effectiveness and cost-effectiveness of the Thinking Healthy Programme delivered by peers (Thinking Healthy Programme Peer-delivered; THPP), for women with moderate to severe perinatal depression in rural and urban settings in Pakistan and India. Methods/Design THPP is evaluated with two randomised controlled trials: a cluster trial in Rawalpindi, Pakistan, and an individually randomised trial in Goa, India. Trial participants are pregnant women who are registered with the lady health workers in the study area in Pakistan and pregnant women attending outpatient antenatal clinics in India. They will be screened using the patient health questionnaire-9 (PHQ-9) for depression symptoms and will be eligible if their PHQ-9 is equal to or greater than 10 (PHQ-9 ≥ 10). The sample size will be 560 and 280 women in Pakistan and India, respectively. Women in the intervention arm (THPP) will be offered ten individual and four group sessions (Pakistan) or 6–14 individual sessions (India) delivered by a peer (defined as a mother from the same community who is trained and supervised in delivering the intervention). Women in the control arm (enhanced usual care) will receive health care as usual, enhanced by providing the gynaecologist or primary-health facilities with adapted WHO mhGAP guidelines for depression treatment, and providing the woman with her diagnosis and information on how to seek help for herself. The primary outcomes are remission and severity of depression symptoms at the 6-month postnatal follow-up. Secondary outcomes include remission and severity of depression symptoms at the 3-month postnatal follow-up, functional disability, perceived social support, breastfeeding rates, infant height and weight, and costs of health care at the 3- and 6-month postnatal follow-ups. The primary analysis will be intention-to-treat. Discussion The trials have the potential to strengthen the evidence on the effectiveness and cost-effectiveness of an evidence-based psychological treatment recommended by the World Health Organisation and delivered by peers for perinatal depression. The trials have the unique opportunity to overcome the shortage of human resources in global mental health and may advance our understanding about the use of peers who work in partnership with the existing health systems in low-resource settings. Trial registration Pakistan Trial: ClinicalTrials.gov Identifier:NCT02111915 (9 April 2014) India Trial: ClinicalTrials.gov Identifier:NCT02104232 (1 April 2014)